Semantic Employment for Doing More in the Verses of the Enemy and Aggression - Khudair Abbas, Sheefa (Opción, 2019)
The aggression is derived from aggression, and it has many indications, including injustice, violation of the limits, and freedom of healing, aggression, aggression, and aggression: injustice, he said: “He who assaulted you and assaulted him like you have been attacked.” [Al-Baqarah: 194]. Ibn al-Arabi stopped at the statement of the significance of the attack in the verse, pointing out that the second attack, like the first in the word and meaning, because it came in the dictionaries in the sense of exceeding the limit and this meaning is included in the two words, but the first is forbidden, and the second ordered, And does not turn the meanings, but he earns what is attached to the description of obe- dience and good, and earns what is attached to the prohibition description of sin and ugliness and both acts exceed the limit, and both acts prevail reality, one right, and the other void).